Concordance between clinical scales and indexes derived from gait analysis studies of in children with cerebral palsy - Uribe, Alejandro; Fernández, Alejandro; Vela, Gustavo (Revista Colombiana de Ortopedia y Traumatología, 2018)
Background: Cerebral Palsy (CP) in children can be classified in terms of function according to several scales, some clinics such as GMFCS (Gross Motor Function Classification System), FMS (functional mobility Scale), FAQ (Gillette Functional Assessment Walking Scale); and others carried out in gait analysis such as the GDI (Gait Deviation Index), GPS (Gait Profile Score). The aim of this study was to determine the concordance between the clinical and gait analysis scales. Methods: 104 children between five and sixteen years old diagnosed with Cerebral palsy were included. A cross sectional and retrospective study analyzed data from three clinical scales of functional mobility and a 3D gait analysis were carried out in gait analysis laboratory, using a SMART-D/BTS equipment and two strength platforms. Results: Regarding the concordance between the scales evaluated, we found that the highest value of kappa (0416), occurred when confronting FAQ and FMS at 50 m, showing a moderate concordance. The remaining values of Kappa when comparing the different scales were smaller than 0.4. While when comparing the scales according to the percentage of agreement we found that the highest percentage was 62.50% when comparing FMS against GPS, followed by 60.50% when comparing FAQ against FMS. Discussion: Not always an acceptable correlation means a high agreement to classify patients at the same level of involvement. The low correlation between most of the scales indicates that the gait analysis in children with Cerebral Palsy should be performed in a complementary manner, performing an assessment with clinical scales, quality of life, and functionality and with instrumented motion analysis. Evidence level. II.